The secret ghost : a mystery with distance and measuring - Thielbar, Melinda (Thielbar, Melinda. Manga math mysteries., 2010)
Sam and his friends at the Kung Fu School use their understanding of width, length, circumference, and volume to uncover the secret of the noises behind the walls of a big Victorian house.